2017
DOI: 10.1177/0271678x17701460
|View full text |Cite
|
Sign up to set email alerts
|

Response of the cerebral vasculature following traumatic brain injury

Abstract: The critical role of the vasculature and its repair in neurological disease states is beginning to emerge particularly for stroke, dementia, epilepsy, Parkinson's disease, tumors and others. However, little attention has been focused on how the cerebral vasculature responds following traumatic brain injury (TBI). TBI often results in significant injury to the vasculature in the brain with subsequent cerebral hypoperfusion, ischemia, hypoxia, hemorrhage, blood-brain barrier disruption and edema. The sequalae th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
189
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(208 citation statements)
references
References 213 publications
5
189
0
6
Order By: Relevance
“…The secreted mitogen bFGF in particular plays an important role in brain repair after injury by promoting proliferation, migration, and survival of endothelial cells . Furthermore, bFGF also stimulates production of vascular endothelial growth factor (VEGF) which acts in conjunction with bFGF to promote angiogenesis . Arteriogenesis and pial collateral vascular remodeling are also carried out by bFGF signaling after cerebral ischemia …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The secreted mitogen bFGF in particular plays an important role in brain repair after injury by promoting proliferation, migration, and survival of endothelial cells . Furthermore, bFGF also stimulates production of vascular endothelial growth factor (VEGF) which acts in conjunction with bFGF to promote angiogenesis . Arteriogenesis and pial collateral vascular remodeling are also carried out by bFGF signaling after cerebral ischemia …”
mentioning
confidence: 99%
“…[30] Furthermore, bFGF also stimulates production of vascular endothelial growth factor (VEGF) which acts in conjunction with bFGF to promote angiogenesis. [27,31] Arteriogenesis and pial collateral vascular remodeling are also carried out by bFGF signaling after cerebral ischemia. [30,32,33] Previous studies have demonstrated that CS-A can support neural stem cells in vitro and transplanted cells in vivo following traumatic brain injury.…”
mentioning
confidence: 99%
“…Increased microvascular permeability is thought to occur via downregulation and/or degradation/ubiquination of tight junction proteins [211-213], and angiogenesis via recruitment of endothelial progenitor cells [214]. VEGF-A is activated by MMP-9, and similarly is also involved in neurogenesis and repair [215], thus making the timing of modulation important to any potential benefit on edema/outcome [80].…”
Section: Molecular Pathophysiology Biomarkers and Targeted Treatmenmentioning
confidence: 99%
“…During TBI, neuronal cell death is not only a paramount contributor to neurological deficits but also a critical factor which seriously affecting the TBI patients’ quality of life. And the neuronal apoptosis after TBI often caused by some secondary events such as hemorrhage, brain edema, and local inflammation . Although there are a significant amount of studies about TBI, there are few effective clinical treatments for TBI patients .…”
Section: Introductionmentioning
confidence: 99%
“…And the neuronal apoptosis after TBI often caused by some secondary events such as hemorrhage, brain edema, and local inflammation. [2][3][4] Although there are a significant amount of studies about TBI, there are few effective clinical treatments for TBI patients. 5 Inadequate understanding of the pathogenesis of neuronal cell death in the damaged area and its surroundings is a major obstacle to the effective treatment of TBI.…”
Section: Introductionmentioning
confidence: 99%